FIRST RESULTS OF CLARIFYING OF ORBITAL ELEMENTS OF LOW-ORBIT SPACECRAFT USING OBSERVATIONS OF THE RI "MAO" DOPPLER STATION - Kriuchkovskyi, V.; Bushuev, F.; Kaliuzhnyi, M.; Khalaley, M.; Kulichenko, M.; Shulga, O. (Одеські астрономічні публікації, 2019)
18 artificial satellites of the Earth, which emit radio signal at a frequency of 430-440 MHz during their flight in the Mykolaiv visibility zone, were found as a result of the searching carried out in the RI "MAO". 10 of 18 satel- lites during not less than 7 days each were automatically tracked by the Doppler station created in the RI “MAO”. The frequency of received radio signal was automatically deter- mined as a result of spectral processing of radio signal ampli- tudes registered by the station during satellite tracking. Herewith 5 of 10 satellites emitted non-harmonic broadband signals. The radial velocity of satellites is calculated using the frequency of received radio signals. The obtained values of radial velocity changing in time were used to clarify TLE (Two-Line Element) orbital el- ements of satellites. Initial orbital elements were down- loaded from the space-track.org site. It would be noted that model values of Doppler shift of frequency, obtained using the initial orbital elements, also use for searching radio signals emitted by tracked satellites and received by the station. The regular (mean) and random (standard de- viation) components of the difference (O-C) of measured and model values of radial velocity were calculated. A comparison of the regular and random components of O-C was made, which showed their slight decreasing after clar- ifying orbital elements. In order to improve the accuracy of the orbit determination, it is proposed to upgrade the station's hardware and software in order to reduce synchronizing and frequency determination errors. It is also proposed to use more accurate models as Dop- pler measurements, and the motion of satellite